Pertanggung Jawaban Pidana Anak Sebagai Pelaku Pembunuhan Di Sebabkan Pengaruh Minuman Keras : (Studi Kepolisian Resor Gorontalo) - Silvana Mointi; Dian Ekawati Ismail; Julisa Aprilia Kaluku (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to examine the criminal responsibility of children as perpetrators of murder caused by the influence of alcohol. Criminal cases involving children as perpetrators of murder are increasing in Indonesia, and one factor that is often the cause is the influence of alcohol. In this research, a study was conducted by the Gorontalo Police to identify the factors that make children perpetrators of murder in this jurisdiction. Internal factors to consider include emotional instability and alcohol use. Emotional instability in children, such as problems with poor emotional control and uncontrollable anger, can make them vulnerable to engaging in violent acts, including murder. Alcohol use also has a significant influence, changing children's behavior to be more aggressive, impulsive and less controlled. Apart from internal factors, this research also involves consideration of the juvenile criminal justice system. Applicable laws, such as Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, regulate sanctions imposed on children based on age differences. The judge has the authority to consider the severity of the act, the child's personal circumstances, or the situation at the time the act was committed or afterwards. This is important to ensure appropriate criminal liability according to the child's circumstances.